Why does interleaving improve math learning? The contributions of discriminative contrast and distributed practice. - Foster, Nathaniel L.; Mueller, Michael L.; Was, Christopher; Rawson, Katherine A.; Dunlosky, John (Memory & Cognition, 2019)
Interleaved practice involves studying exemplars from different categories in a non-systematic, pseudorandom order under the constraint that no two exemplars from the same category are presented consecutively. Interleaved practice of materials has been shown to enhance test performance compared to blocked practice in which exemplars from the same category are studied together. Why does interleaved practice produce this benefit? We evaluated two non-mutually exclusive hypotheses, the discriminative-contrast hypothesis and the distributed-practice hypothesis, by testing participants' performance on calculating the volume of three-dimensional geometric shapes. In Experiment 1, participants repeatedly practiced calculating the volume of four different-sized shapes according to blocked practice, interleaved practice, or remote-interleaved practice (which involved alternating the practice of volume calculation with non-volume problems, like permutations and fraction addition). Standard interleaving enhanced performance compared to blocked practice but did not produce enhanced performance compared to remote interleaving. In Experiment 2, we replicated this pattern and extended the results to include a remote-blocked group, which involved blocking volume calculation with non-volume problems. Performance on key measures was better for remote-interleaved groups compared to remote-blocked groups, a finding that supports the distributed-practice hypothesis.